Papéis molhados e outros contos : a construção de um espaço narrativo na ficção - Müller, Iuri Almeida (2016)
The present Master’s thesis is composed by eleven fiction narratives, of the short story genre, a set in which unit is established through the attention of construction from the narrative spaces in those texts – in that case, the urban spaces such as Porto Alegre, Santa Maria, Montevideo, Buenos Aires and Lisbon. In theoretical terms, this paper intends to analyze the manner in which the urban space appears in the first phase from the Uruguayan writer Juan Carlos Onetti, as well as the elements used in the literary construction of Santa Maria, fictional city created by Onetti, present in his short stories and novel, such as A vida breve. Likewise, in a dialogue between creation and reflection, maps are utilized in order to observe the displacement of the characters in three of the short narratives that encompass this set of creation.